Drop-out to follow up screening of diabetes mellitus in Indonesia from national health insurance data 2022-2024 - Kresnowati Lily; Suhartono Suhartono; Shaluhiyah Zahroh; Widjanarko Bagoes (E3S Web of Conferences)
Diabetes poses a significant public health challenge, particularly in Indonesia where 10.7 million people are affected, and this is predicted to increase to 13.7 million by 2030. Diabetes rates in Indonesia continue to rise and are predicted to affect younger age groups, highlighting the need to strengthen preventive efforts, one of which is conducting earlier DM screening. This study examines the dropout rates in follow-up screenings for diabetes mellitus (DM) among members of Indonesia’s National Health Insurance (BPJS) from 2022 to June 2024. The research utilizes a descriptive method. The research variables are the number of BPJS membership, the percentage of Health screening, the percentage of DM risk from screening, the number of follow up, and the results of DM test. The analysis technique uses descriptive analysis. Nationally, the follow-up rate of screening increase from 1.81% in 2022 to 1.98% in 2023. Despite a slight recovery to 1.25% by mid-2024. The mean of follow-up rate nationally to 1.73%. These findings indicate the need for educational campaigns to raise awareness about the importance of DM screening and follow-up care. Further research is necessary to conduct a partial analysis related to community characteristics and factors influencing follow-up screening for DM.